Polylactic acid core-shell structure fiber membrane as well as preparation method and application thereof
Through the formation of a polylactic acid nuclear shell structure in the fiber membrane and adding electrolytes, the problem of low electrical energy of polylactic acid fiber membrane is solved, and the effect of high -efficiency filtration and self -power supply is achieved, while maintaining biocompatibility and degradability.
Patent Information
- Application Number
- CN202411675409.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polylactic fiber membranes have low dielectric constant, low piezoelectric constant, low surface potential and poor charge storage capacity, resulting in attenuation of filtration efficiency.
By using the first clustering lactic acid and second clustering lactic acid as the shell layer and the nuclear layer of spinning solution, the coaxial static spinning wire is formed to form a fiber film of the ribin -shell structure of polymapilic acid, and the electrolyte is added to the spinning solution to optimize the fibrous membrane Electricity and charge storage capacity.
It improves the dielectric constant of the fiber membrane, the piezoelectric constant, the surface potential, and the charge storage capacity, enhance the filtering performance, and give self -power supply characteristics, maintaining good biocompatibility and degradability.
Smart Images

Figure CN119372838A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber membranes, and in particular to a polylactic acid core-shell structure fiber membrane and a preparation method and application thereof. Background Art
[0002] Particulate matter (PM) in the air has a huge negative impact on nature and human health. PM can be divided into coarse components (PM with a diameter <10 μm) according to its diameter. 10 ), fine components (PM with a diameter <2.5 μm 2.5 ) and ultrafine components (UFPS with a diameter of <0.1 μm), these particles can penetrate the respiratory system and even enter the blood, causing health hazards. Therefore, there is an urgent need for a filter medium for personal protection, such as masks, to protect the public from industrial particulate matter and air pollution.
[0003] At present, the main air filter materials for personal protection are melt-blown electrostatically charged nonwoven materials, and electrets with charge storage capacity are added to conventional filter materials to increase the electrostatic adsorption effect. However, electrets are easily affected by the use time and environmental humidity, which causes their charge to dissipate, affecting their filtration efficiency under long-term use, and most filter materials cannot be naturally degraded, which puts great pressure on the garbage disposal system and the ecological environment.
[0004] At present, polylactic acid (PLA) has attracted widespread attention due to its advantages such as good biocompatibility, biodegradability, high mechanical strength and easy processing. However, PLA fiber membrane has problems such as low dielectric constant, low piezoelectric constant, low surface potential, poor charge storage capacity, etc., which leads to serious attenuation of filtration efficiency. Summary of the invention
[0005] The main purpose of the present invention is to provide a polylactic acid core-shell structure fiber membrane and its preparation method and application, so as to solve the problem in the prior art that the polylactic acid fiber membrane has low dielectric constant, low piezoelectric constant, low surface potential and poor charge storage capacity, which affects the filtration performance.
[0006] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a polylactic acid core-shell structure fiber membrane is provided, comprising the following steps:
[0007] S1, mixing a first polylactic acid, an electrolyte and a first solvent to obtain a first polylactic acid solution;
[0008] S2, mixing the second polylactic acid with the second solvent to obtain a second polylactic acid solution;
[0009] S3, using the first polylactic acid solution and the second polylactic acid solution as a shell layer spinning solution and a core layer spinning solution, respectively, to perform coaxial electrospinning to obtain a polylactic acid core-shell structure fiber membrane;
[0010] The first polylactic acid and the second polylactic acid are independently selected from at least one of left-handed polylactic acid and right-handed polylactic acid. The first polylactic acid solution and the second polylactic acid solution are used as a composite solution, and the composite solution contains left-handed polylactic acid and right-handed polylactic acid.
[0011] Furthermore, the electrolyte includes at least one of potassium chloride, sodium chloride, lithium chloride, and calcium chloride.
[0012] Furthermore, the mass ratio of the first polylactic acid to the electrolyte is (0.1-1):1.
[0013] Further, the mass ratio of the first polylactic acid to the second polylactic acid is (0.5-2):1; and / or,
[0014] In the compound solution, the mass ratio of L-polylactic acid to D-polylactic acid is 1:(0-1);
[0015] Preferably, the first polylactic acid is the L-polylactic acid, and the second polylactic acid is the D-polylactic acid.
[0016] Alternatively, the first polylactic acid is dextrorotatory polylactic acid, and the second polylactic acid is laxtrorotatory polylactic acid;
[0017] Alternatively, the L-polylactic acid is divided into a first portion of L-polylactic acid and a second portion of L-polylactic acid, the first polylactic acid is the first portion of L-polylactic acid, and the second polylactic acid is a mixture of the second portion of L-polylactic acid and D-polylactic acid;
[0018] Alternatively, the L-polylactic acid is divided into a first portion of L-polylactic acid and a second portion of L-polylactic acid, the second portion of L-polylactic acid is the first portion of L-polylactic acid, and the first portion of L-polylactic acid is a mixture of the second portion of L-polylactic acid and D-polylactic acid;
[0019] Alternatively, the dextrorotatory polylactic acid is divided into a first part of dextrorotatory polylactic acid and a second part of dextrorotatory polylactic acid, the first polylactic acid is the first part of dextrorotatory polylactic acid, and the second polylactic acid is a mixture of the second part of dextrorotatory polylactic acid and laetrorotatory polylactic acid;
[0020] Alternatively, the dextrorotatory polylactic acid is divided into a first portion of dextrorotatory polylactic acid and a second portion of dextrorotatory polylactic acid, the second portion of polylactic acid is the first portion of dextrorotatory polylactic acid, and the first portion of polylactic acid is a mixture of the second portion of dextrorotatory polylactic acid and laetrorotatory polylactic acid.
[0021] Further, the mass fraction of the first polylactic acid in the first polylactic acid solution is 0.1% to 15%; and / or,
[0022] The mass fraction of the second polylactic acid in the second polylactic acid solution is 0.1% to 15%; and / or,
[0023] The concentration of the electrolyte in the first polylactic acid solution is 0.01 to 1 g / mL.
[0024] Furthermore, the first solvent and the second solvent each independently include at least one of dichloromethane, chloroform, N,N-dimethylformamide, acetone, ethyl acetate, and ethanol.
[0025] Furthermore, in the coaxial electrospinning process, the metal nozzles loaded with the shell layer spinning solution and the core layer spinning solution are respectively the first nozzle and the second nozzle;
[0026] Preferably, the inner diameter of the first nozzle is 0.5 to 1 mm, and the inner diameter of the second nozzle is 1.2 to 1.5 mm;
[0027] Preferably, the voltage of the first nozzle and the second nozzle is independently 5 to 50 kV;
[0028] Preferably, the consumption rate of the shell layer spinning solution is 1 to 5 mL / h, and the consumption rate of the core layer spinning solution is 1 to 5 mL / h;
[0029] Preferably, the receiving distances of the first nozzle and the second nozzle are independently 10 to 50 cm, and the wire collection speed is 100 to 5000 rpm.
[0030] The second aspect of the present invention provides a polylactic acid core-shell structure fiber membrane, which is prepared by the preparation method provided by the first aspect.
[0031] Furthermore, the average diameter of the fibers in the polylactic acid core-shell structure fiber membrane is 100 to 300 nm;
[0032] Preferably, the average diameter of the fibers in the polylactic acid core-shell structure fiber membrane is 155 to 235 nm.
[0033] The third aspect of the present invention provides a personal protective device, comprising the polylactic acid core-shell structure fiber membrane provided by the second aspect.
[0034] By applying the technical scheme of the present invention, by controlling the combination of the first polylactic acid and the second polylactic acid and the use of electrolytes, and utilizing coaxial electrospinning, a unique core-shell structure can be formed, and a unique stereocomposite structure can be formed in the shell layer or the core layer. At the same time, the electrical activity and charge storage capacity of the fiber membrane are enhanced, and the fiber membrane is endowed with the characteristic of self-power supply, so that the prepared fiber membrane has excellent dielectric constant, piezoelectric constant, surface potential and charge storage capacity, so that the fiber membrane has high-efficiency filtration performance while maintaining good biocompatibility and degradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a SEM image of the polylactic acid core-shell structure fiber membrane in Example 1 of the present invention;
[0036] Figure 2 This is the SEM image of the polylactic acid fiber membrane in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0038] As described in the background of the present invention, the prior art has no solution to the problem that the polylactic acid fiber membrane in the prior art has low dielectric constant, low piezoelectric constant, low surface potential, and poor charge storage capacity, which affects the filtration performance. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a polylactic acid core-shell structure fiber membrane is provided, comprising the following steps:
[0039] S1, mixing a first polylactic acid, an electrolyte and a first solvent to obtain a first polylactic acid solution;
[0040] S2, mixing the second polylactic acid with the second solvent to obtain a second polylactic acid solution;
[0041] S3, using the first polylactic acid solution and the second polylactic acid solution as a shell layer spinning solution and a core layer spinning solution, respectively, to perform coaxial electrospinning to obtain a polylactic acid core-shell structure fiber membrane;
[0042] The first polylactic acid and the second polylactic acid are independently selected from at least one of left-handed polylactic acid and right-handed polylactic acid. The first polylactic acid solution and the second polylactic acid solution are used as a composite solution, and the composite solution contains left-handed polylactic acid and right-handed polylactic acid.
[0043] The present invention utilizes coaxial electrospinning technology to form a unique core-shell structure, wherein the first polylactic acid and the electrolyte in the first polylactic acid solution can form a shell layer, and the second polylactic acid in the second polylactic acid solution can form a core layer. The fiber membrane with the core-shell structure has high structural stability, which helps the fiber membrane maintain its filtration performance and charge stability under different environmental conditions (such as humidity changes), thereby extending its service life.
[0044] Levorotatory polylactic acid (PLLA) and dextrorotatory polylactic acid (PDLA) can form a stereocomplex (SC-PLA) complex, which is a β-crystal with high electrical activity (including surface potential, dielectric constant and piezoelectric constant) and charge storage capacity. It can convert environmental mechanical energy such as respiratory vibration, human movement and sound waves into electrical energy through friction electrification and electrostatic induction effects to continuously inject charges. By controlling the combination of the first polylactic acid and the second polylactic acid, a unique stereocomplex structure is formed in the shell layer, core layer or core-shell interface of the core-shell structure, thereby enhancing its electrostatic adsorption capacity and filtration performance.
[0045] The first polylactic acid and the second polylactic acid can be independently selected from at least one of left-handed polylactic acid and right-handed polylactic acid, and it is ensured that when the first polylactic acid solution and the second polylactic acid solution are used as the composite solution, the composite solution contains left-handed polylactic acid and right-handed polylactic acid. For example, when the first polylactic acid only includes left-handed polylactic acid, the second polylactic acid can only include right-handed polylactic acid, or the second polylactic acid includes both left-handed polylactic acid and right-handed polylactic acid; when the first polylactic acid only includes right-handed polylactic acid, the second polylactic acid can only include left-handed polylactic acid, or the second polylactic acid includes both left-handed polylactic acid and right-handed polylactic acid.
[0046] Electrolyte refers to a compound that can conduct electricity when dissolved in water or in a molten state. Such compounds decompose into positively charged cations and negatively charged anions when dissolved or melted, and these ions can move under the action of an electric field, thereby conducting electricity. The present invention introduces an electrolyte into the first polylactic acid solution. First, its function is to increase the conductivity of the shell spinning solution. In the subsequent coaxial electrospinning process, the conductivity of the shell spinning solution has an important influence on the formation and performance of the fiber. The higher conductivity helps the solution to better form a stable Taylor cone, helps to generate a more stable electrospinning jet in a high-voltage electrostatic field, and can prepare finer and more uniform fibers, thereby improving the filtration performance of the fiber membrane; secondly, the electrolyte can increase the charge density on the fiber surface, thereby improving the electrostatic adsorption capacity of the fiber, and the fiber with a high charge density can more effectively capture particulate matter in the air, thereby improving the filtration efficiency; in addition, the electrolyte can provide a stable ionic environment, which helps the fiber membrane to maintain or enhance its surface potential under different environmental conditions (such as humidity changes), maintain or maintain the charge stability of the fiber membrane, and help to ensure the long-term use and performance stability of the fiber membrane. In addition, in the above-mentioned nanofibers with core-shell structure and stereocomplex, the addition of electrolytes can further optimize the piezoelectric properties of the fiber membrane, that is, the ability to convert mechanical energy into electrical energy. This makes the fiber membrane not only a high-efficiency air filtration material, but also can produce a self-powered effect during use, further improving the filtration efficiency.
[0047] According to the research of the present invention, the polylactic acid core-shell structure fiber membrane prepared by the above-mentioned preparation method has excellent filtration performance. This is because, by controlling the combination of the first polylactic acid and the second polylactic acid and the use of electrolytes, and utilizing coaxial electrospinning, a unique core-shell structure can be formed, and a unique stereocomposite structure is formed in the shell layer, the core layer or the core-shell interface. At the same time, the electrical activity and charge storage capacity of the fiber membrane are enhanced, and the fiber membrane is endowed with self-powered characteristics, so that the prepared fiber membrane has excellent dielectric constant, piezoelectric constant, surface potential and charge storage capacity, so that the fiber membrane has high-efficiency filtration performance while maintaining good biocompatibility and degradability.
[0048] The structure and filtration performance of the electrospun fiber membrane can be improved by adding an electrolyte, and the electrolyte can be a commonly used inorganic electrolyte. In some embodiments, the electrolyte includes at least one of potassium chloride, sodium chloride, lithium chloride, and calcium chloride. These high-conductivity electrolytes help to produce a more stable electrospinning jet in a high-voltage electrostatic field, thereby facilitating the preparation of fibers with excellent performance.
[0049] In some embodiments, the mass ratio of the first polylactic acid to the electrolyte is (0.1-1):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or any two of them. By limiting the mass ratio of the first polylactic acid to the electrolyte within a suitable range, the presence of the electrolyte helps the fiber to be further refined under the action of the electric field. The fine fibers have a higher specific surface area, which can increase the contact area between the fiber membrane and the air flow, thereby improving the filtration efficiency while maintaining a low air resistance. In addition, by adjusting the mass ratio of the first polylactic acid to the electrolyte, the microstructure of the fiber membrane, such as fiber diameter, porosity, etc., and macroscopic properties, such as surface potential, dielectric constant, piezoelectric constant, etc., can be precisely controlled, thereby preparing a fiber membrane with better performance and more in line with specific application requirements.
[0050] In some embodiments, the mass ratio of the first polylactic acid to the second polylactic acid is (0.5-2):1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.2:1, 1.6:1, 1.8:1, 2:1 or a range consisting of any two of them. By controlling the mass ratio of the first polylactic acid to the second polylactic acid, the microstructure of the fiber membrane can be optimized to form different microstructures, including the average diameter, porosity and morphology of the fiber. These structural changes directly affect the filtration efficiency and air resistance of the fiber membrane. By controlling the mass ratio of the first polylactic acid to the second polylactic acid within the above range, it is ensured that the fiber membrane can achieve high filtration efficiency while maintaining low air resistance, meeting the needs of efficient air filtration.
[0051] When PLLA and PDLA are blended at a certain ratio, a stereocomplex (SC-PLA) can be formed, which can increase the surface potential and dielectric constant of the fiber membrane, thereby enhancing its electrostatic adsorption capacity and filtration performance. In some embodiments, in the compound solution, the mass ratio of left-handed polylactic acid to right-handed polylactic acid is 1: (0-1), for example, 1: 0.1, 1: 0.2, 1: 0.3, 1: 0.4, 1: 0.5, 1: 0.6, 1: 0.7, 1: 0.8, 1: 0.9, 1: 1 or the range of any two of them. By limiting the mass ratio of left-handed polylactic acid to right-handed polylactic acid within a suitable range and ensuring the formation of a stereocomplex of a suitable ratio, the electrical activity of the fiber membrane can be further improved, including increasing the surface potential, dielectric constant and piezoelectric constant, which is beneficial to the application of the fiber membrane as a high-efficiency air filtration material, and can more effectively capture particulate matter. At the same time, it has a self-powered performance, that is, it can convert mechanical energy such as breathing vibration into electrical energy. Secondly, by controlling the ratio of PLLA to PDLA, the toughness and strength of the fiber membrane can be adjusted to make it more suitable for applications such as air filtration. In addition, the degradation rate and pattern of polylactic acid are affected by its molecular structure. By adjusting the ratio of PLLA to PDLA, the biodegradability of the fiber membrane can be designed so that it can be degraded in a more environmentally friendly way after reaching the end of its service life, reducing the impact on the environment.
[0052] Specifically, in one embodiment, the first polylactic acid is left-handed polylactic acid, and the second polylactic acid is right-handed polylactic acid; or, the first polylactic acid is right-handed polylactic acid, and the second polylactic acid is left-handed polylactic acid; or, the left-handed polylactic acid is divided into a first part of left-handed polylactic acid and a second part of left-handed polylactic acid, the first polylactic acid is the first part of left-handed polylactic acid, and the second polylactic acid is a mixture of the second part of left-handed polylactic acid and right-handed polylactic acid; or, the left-handed polylactic acid is divided into a first part of left-handed polylactic acid and a second part of left-handed polylactic acid, the second polylactic acid is the first part of left-handed polylactic acid, and the first polylactic acid is a mixture of the second part of left-handed polylactic acid and right-handed polylactic acid; the mass of the left-handed polylactic acid is the sum of the masses of the first part of the left-handed polylactic acid and the second part of the left-handed polylactic acid. Alternatively, the dextrorotatory polylactic acid is divided into a first part dextrorotatory polylactic acid and a second part dextrorotatory polylactic acid, the first polylactic acid is the first part dextrorotatory polylactic acid, and the second polylactic acid is a mixture of the second part dextrorotatory polylactic acid and left-handed polylactic acid; or, the dextrorotatory polylactic acid is divided into a first part dextrorotatory polylactic acid and a second part dextrorotatory polylactic acid, the second polylactic acid is the first part dextrorotatory polylactic acid, the first polylactic acid is a mixture of the second part dextrorotatory polylactic acid and left-handed polylactic acid, and the mass of the dextrorotatory polylactic acid is the sum of the masses of the first part dextrorotatory polylactic acid and the second part dextrorotatory polylactic acid.
[0053] The mass fraction of polylactic acid in the polylactic acid solution directly affects the viscosity and surface tension of the spinning solution, thereby affecting the formation of fibers during the electrospinning process. In some embodiments, the mass fraction of the first polylactic acid in the first polylactic acid solution is 0.1% to 15%. In some embodiments, the mass fraction of the second polylactic acid in the second polylactic acid solution is 0.1% to 15%. By controlling the appropriate mass fraction, it is helpful to prepare nanofibers with uniform diameter and good stability. Secondly, the adjustment of the mass fraction can affect the porosity and density of the fiber membrane, thereby affecting its filtration performance and air resistance. By controlling the above-mentioned appropriate mass fraction, it is helpful to form a fiber membrane structure with high porosity and low air resistance, which is particularly important for air filtration applications. It can improve the filtration efficiency while maintaining a low pressure drop; in addition, the mass fraction of polylactic acid has a direct impact on the process conditions of electrospinning. By controlling the mass fraction of polylactic acid within the above range, the spinning process can be ensured to be stable, thereby improving the production efficiency and quality of the fiber membrane.
[0054] The addition of electrolyte increases the conductivity of the spinning solution, and the concentration of the electrolyte is directly related to the dielectric constant and piezoelectric properties of the fiber membrane. In some embodiments, the concentration of the electrolyte in the first polylactic acid solution is 0.01 to 1 g / mL. By controlling the concentration of the electrolyte in the first polylactic acid solution within the above-mentioned suitable range, it helps to optimize the dielectric and piezoelectric properties of the fiber membrane and further improve the filtration performance of the fiber membrane.
[0055] The present invention does not limit the specific types of the first solvent and the second solvent, which can be conventional organic solvents in the art. For example, in some embodiments, the first solvent and the second solvent each independently include at least one of dichloromethane, chloroform, N,N-dimethylformamide, acetone, ethyl acetate, and ethanol.
[0056] In the coaxial electrospinning process, the shell layer spinning solution and the core layer spinning solution need to be loaded into the container of the nozzle respectively, and ensure that the aperture of the nozzle meets the required fiber size. In some embodiments, in the coaxial electrospinning process, the metal nozzles loaded with the shell layer spinning solution and the core layer spinning solution are the first nozzle and the second nozzle respectively; the inner diameter of the first nozzle is 0.5-1 mm, and the inner diameter of the second nozzle is 1.2-1.5 mm.
[0057] In addition, during the coaxial electrospinning process, a high voltage electrostatic field needs to be applied to charge the spinning solution. According to the properties and viscosity of the spinning solution, a suitable voltage range is selected. In some embodiments, the voltage of the first nozzle and the second nozzle is independently 5 to 50 kV;
[0058] By limiting the consumption rate of the shell layer spinning solution and the core layer spinning solution, the preparation of fiber membranes with different diameters can be achieved. In some embodiments, the consumption rate of the shell layer spinning solution is 1-5 mL / h, and the consumption rate of the core layer spinning solution is 1-5 mL / h.
[0059] The receiving device of coaxial electrospinning can be a rotating drum, a flat plate or a mesh structure, etc. The distance of the receiving device will affect the deposition morphology and arrangement of the fibers. In some embodiments, the receiving distances of the first nozzle and the second nozzle are independently 10 to 50 cm, and the collection rate is 100 to 5000 rpm. In the coaxial spinning process, the collection rate (also called the receiving rate or the collection rate) refers to the speed at which the device for receiving the fiber membrane rotates. This speed determines the deposition rate and thickness of the fiber membrane on the collecting substrate. The above-mentioned collection rate refers to the number of rotations per unit time, which ensures that the fibers have enough time to be evenly distributed on the substrate. The collection rate within the above-mentioned appropriate range can help the fibers form a more dense and orderly structure on the substrate, thereby improving the mechanical properties and filtration performance of the fiber membrane.
[0060] In some embodiments, the spinning temperature is 20-45° C., and the relative humidity of the environment is 25%-45%.
[0061] The second aspect of the present invention provides a polylactic acid core-shell structure fiber membrane, which is prepared by the preparation method provided by the first aspect.
[0062] The polylactic acid core-shell structure fiber membrane prepared by the above preparation method of the present invention not only has excellent air filtration performance, but also has self-power supply capability, good biocompatibility and degradability. This material can be widely used in personal protective equipment, air purification systems, etc.
[0063] Specifically, the surface potential of the polylactic acid core-shell structure fiber membrane is 8.9 to 10.7 kV. This high voltage value has a strong electrostatic adsorption effect on particulate matter, so that the fiber membrane can not only physically intercept tiny particles, but also enhance the filtration effect through electrostatic action; and / or, the piezoelectric constant (d33) of the polylactic acid core-shell structure fiber membrane is between 6.6 and 8.3 pC / N, which means that the fiber membrane can convert mechanical energy (such as breathing vibration, human body movement) into electrical energy; the polylactic acid core-shell structure fiber membrane has self-powered power supply capability. In the state of simulating human breathing, the fiber membrane can output a voltage of 8.7 to 12.4 V, an output current of 0.87 to 1.12 μA and a charge density of 16.5 to 25.3 μC / m 2 , indicating that it can self-charge during use, maintain surface charge, and continuously and efficiently filter the air; the air resistance of the polylactic acid core-shell structure fiber membrane is less than 180Pa, maintaining low barrier properties, allowing the wearer to breathe smoothly. The polylactic acid core-shell structure fiber membrane has excellent filtration performance and is effective for PM 0.3(particles with a diameter less than 0.3 μm) and PM 2.5 The filtration efficiency of the two filters (particles with a diameter less than 2.5 μm) is extremely high, greater than 96% and 98% respectively, and is particularly good at a gas flow rate of 85 L / min.
[0064] In addition, the fiber membrane is made of polylactic acid, which is a bio-based degradable material, which means that the fiber membrane can be naturally degraded after use, reducing the impact on the environment and the burden on the garbage disposal system; polylactic acid has good biocompatibility, which allows the fiber membrane to be in contact with the skin for a long time when used in personal protective equipment (such as masks) without causing allergic or irritation reactions, making it suitable for long-term wear; due to the high filtration efficiency, low air resistance and degradability of the fiber membrane, it can achieve environmental sustainability.
[0065] In some embodiments, the average diameter of the fibers in the polylactic acid core-shell structure fiber membrane is 100-300 nm, and the ultrafine fiber structure of the fiber membrane ensures high porosity and reduces pressure drop. In some preferred embodiments, the average diameter of the fibers in the polylactic acid core-shell structure fiber membrane is 155-235 nm.
[0066] The third aspect of the present invention provides a personal protective device, comprising the polylactic acid core-shell structure fiber membrane provided by the second aspect.
[0067] Personal protective equipment, such as masks, has extremely high PM 0.3 and PM 2.5 The filtration efficiency is greater than 96% and 98% respectively, which can effectively block tiny particles in the air, and the air resistance of the fiber membrane is less than 180Pa, which makes the mask have low breathing resistance when worn, more comfortable, suitable for long-term wear, and reduces the risk of the wearer taking off the mask due to poor breathing; the fiber membrane has piezoelectric properties, which can convert mechanical energy into electrical energy, and can output voltage, current and charge density in the breathing state. This self-powered performance means that the mask can continuously replenish the charge on the surface of the fiber membrane during use, maintain its efficient electrostatic adsorption ability, and the filtration efficiency will not decrease significantly even after long-term use. In addition, because the fiber membrane is made of polylactic acid, it has good biocompatibility and degradability, and can be naturally degraded after being discarded, reducing the impact on the environment.
[0068] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0069] Example 1
[0070] The method for preparing the polylactic acid core-shell structure fiber membrane of this embodiment comprises the following steps:
[0071] S11, preparing a shell spinning solution: dissolving 0.1 g of right-handed polylactic acid in 10 mL of dichloromethane / chloroform (mass ratio is 4:6), stirring and adding 0.1 g of potassium chloride to obtain a first polylactic acid solution, which is used as a shell spinning solution;
[0072] S12, preparing a core layer spinning solution: dissolving 1.5 g of L-polylactic acid in 10 mL of chloroform / dichloromethane (mass ratio is 2:8), stirring to obtain a second polylactic acid solution, which is used as the core layer spinning solution;
[0073] S13, preparation of stereocomposite polylactic acid core-shell structure fiber filtration membrane: coaxially electrospin 1 mL of shell layer spinning solution and 5 mL of core layer spinning solution, the electrospinning voltage is 20 kV, the shell layer spinning solution consumption rate is 5 mL / h, the core layer spinning solution consumption rate is 1 mL / h, the receiving distance is 10 cm, and the collection rate is 100 rpm.
[0074] Example 2
[0075] The method for preparing the polylactic acid core-shell structure fiber membrane of this embodiment comprises the following steps:
[0076] S21, preparing a shell electrospinning solution: dissolving 1.5 g of L-polylactic acid in 10 mL of acetone / ethyl acetate (mass ratio of 8:2), stirring and adding 10 g of sodium chloride to obtain a first polylactic acid solution, which is used as a shell spinning solution;
[0077] S22, preparing a core layer polylactic acid spinning solution: dissolving 0.1 g of dextrorotatory polylactic acid in 10 mL of chloroform / N,N-dimethylformamide (mass ratio is 3:7), stirring to obtain a second polylactic acid solution, which is used as the core layer spinning solution;
[0078] S23, preparation of stereocomposite polylactic acid core-shell structure fiber filtration membrane: coaxially electrospin 5mL of shell layer spinning solution and 1mL of core layer spinning solution, the electrospinning voltage is 50kV, the shell layer spinning solution consumption rate is 1mL / h, the core layer spinning solution consumption rate is 5mL / h, the receiving distance is 30cm, and the collection rate is 1000rpm.
[0079] Example 3
[0080] The method for preparing the polylactic acid core-shell structure fiber membrane of this embodiment comprises the following steps:
[0081] S31, preparing a shell electrospinning solution: dissolving 1 g of dextrorotatory polylactic acid in 10 mL of dichloromethane, stirring and adding 1 g of lithium chloride to obtain a first polylactic acid solution, which is used as a shell spinning solution;
[0082] S32, preparing a core layer polylactic acid spinning solution: dissolving 1 g of L-polylactic acid and 1 g of D-polylactic acid in 10 mL of dichloromethane / N,N-dimethylformamide (mass ratio of 7:3), respectively, and stirring to obtain a second polylactic acid solution, which is used as the core layer spinning solution;
[0083] S33, preparation of stereocomposite polylactic acid core-shell structure fiber filtration membrane: coaxially electrospin 2mL of shell layer spinning solution and 2mL of core layer spinning solution, the electrospinning voltage is 30kV, the shell layer spinning solution consumption rate is 1mL / h, the core layer spinning solution consumption rate is 1mL / h, the receiving distance is 15cm, and the collection rate is 300rpm.
[0084] Example 4
[0085] The method for preparing the polylactic acid core-shell structure fiber membrane of this embodiment comprises the following steps:
[0086] S41, preparing a shell electrospinning solution: dissolving 1 g of L-polylactic acid and 0.5 g of D-polylactic acid in 10 mL of chloroform, respectively, stirring and adding 0.8 g of sodium chloride to obtain a first polylactic acid solution, which is used as a shell spinning solution;
[0087] S42, preparing a core layer polylactic acid spinning solution: dissolving 2 g of L-polylactic acid in 10 mL of chloroform / ethanol (mass ratio is 7:3), stirring to obtain a second polylactic acid solution, which is used as the core layer spinning solution;
[0088] S43, preparation of stereocomposite polylactic acid core-shell structure fiber filtration membrane: coaxially electrospin 3mL of shell layer spinning solution and 1mL of core layer spinning solution, the electrospinning voltage is 50kV, the shell layer spinning solution consumption rate is 1mL / h, the core layer spinning solution consumption rate is 3mL / h, the receiving distance is 20cm, and the collection rate is 500rpm.
[0089] Example 5
[0090] The method for preparing the polylactic acid core-shell structure fiber membrane of this embodiment comprises the following steps:
[0091] S51, preparing a shell electrospinning solution: dissolving 1 g of dextrorotatory polylactic acid in 10 mL of chloroform, stirring and adding 2 g of calcium chloride to obtain a first polylactic acid solution, which is used as a shell spinning solution;
[0092] S52, preparing a core layer polylactic acid spinning solution: dissolving 1 g of L-polylactic acid and 1 g of D-polylactic acid in 10 mL of chloroform / ethanol (mass ratio of 7:3), stirring, and obtaining a first polylactic acid solution, which is used as a shell layer spinning solution;
[0093] S53, preparation of stereocomposite polylactic acid core-shell structure fiber filtration membrane: coaxially electrospin 3mL of shell layer spinning solution and 1mL of core layer spinning solution, the electrospinning voltage is 50kV, the shell layer spinning solution consumption rate is 1mL / h, the core layer spinning solution consumption rate is 3mL / h, the receiving distance is 20cm, and the collection rate is 500rpm.
[0094] Comparative Example 1
[0095] The preparation method of the polylactic acid fiber film of this comparative example comprises the following steps:
[0096] 3 g of L-polylactic acid was dissolved in 10 mL of chloroform / dichloromethane (mass ratio of 2:8), and 1 mL of spinning solution was taken for electrospinning. The spinning voltage was 20 kV, the spinning solution consumption rate was 5 mL / h, the receiving distance was 10 cm, and the spinning rate was 100 rpm.
[0097] Comparative Example 2
[0098] The preparation method of the polylactic acid fiber film of this comparative example comprises the following steps:
[0099] 3 g of right-handed polylactic acid was dissolved in 10 mL of acetone / ethyl acetate (mass ratio of 8:2), and 10 g of sodium chloride was added. 1 mL of spinning solution was taken for electrospinning. The electrospinning voltage was 50 kV, the spinning solution consumption rate was 5 mL / h, the receiving distance was 30 cm, and the collection rate was 1000 rpm.
[0100] Comparative Example 3
[0101] The preparation method of the polylactic acid fiber film of this comparative example comprises the following steps:
[0102] 1 g of L-polylactic acid was dissolved in 10 mL of dichloromethane / N,N-dimethylformamide (mass ratio of 7:3), 1 g of D-polylactic acid was dissolved in 10 mL of dichloromethane, and 1 g of lithium chloride was added. 2 mL of L-polylactic acid solution and 2 mL of D-polylactic acid solution were mixed and then electrospun. The electrospinning voltage was 30 kV, the spinning solution consumption rate was 1 mL / h, the receiving distance was 15 cm, and the drum speed was 300 rpm.
[0103] Test example
[0104] 1. Fiber average diameter test
[0105] A field emission scanning electron microscope (SU8220, Hitachi, Japan) was used to observe the surface structure of the fiber membrane and measure the fiber diameter. 100 different fibers were taken from each sample, the fiber diameter was calculated, and the average value was taken, which was the average fiber diameter.
[0106] 2. Surface potential test
[0107] The surface potential of the nanofiber membrane was measured using a non-contact electrostatic meter (VM54XQS, Quatek, USA). The fiber membrane sample was cut into 2×2 cm and placed on an antistatic pad (Bertech, 1059-2X3BKT) to improve the accuracy of the measurement; the probe was grounded to ensure that the test distance was 5 mm, and each sample was tested 3 times to take the average value.
[0108] 3. Dielectric constant test
[0109] The dielectric constant of the fiber membrane was tested using a dielectric constant tester (WK-6500B, Wayne Kerr Company, UK), and copper electrodes were evenly covered on both sides of the fiber membrane to ensure good conductivity when measuring the dielectric constant.
[0110] 4. Filtration performance test
[0111] The air filtration performance of the fiber membrane (diameter 10 cm) was tested using an automatic filter material tester (TSI8130, USA), the gas flow rate was set to 85 L / min, and its air resistance was tested. The particle size range of the NaCl atomized particles produced by the aerosol generator was 0.1 to 10 μm. At least 3 different positions of each group of fiber membranes were tested, and the results were averaged.
[0112] 5. Piezoelectric performance test
[0113] The piezoelectric coefficient (d33) of the fiber membrane was measured using a piezoelectric constant tester (ZJ-3BN, Institute of Acoustics, Chinese Academy of Sciences, Beijing).
[0114] 6. Breathing vibration self-powered performance test
[0115] A humanoid respirator (YY / T 0735.1, Shanghai Chengsi Intelligent Technology Co., Ltd., Shanghai) was used to simulate the normal breathing state of a human, and the gas flow rate was set to 32 L / min to test its filtration performance, and an electrometer tester (6514, Keithley, USA) was used to test the output electrical performance of the fiber membrane under the breathing state.
[0116] The test results are shown in Table 1 and Table 2.
[0117] Table 1
[0118]
[0119]
[0120] Table 2
[0121]
[0122] Figure 1 and Figure 2 They are SEM images of the fiber membranes of Example 1 and Comparative Example 1, respectively. Table 1 compares the test results of the average fiber diameter, surface potential, dielectric constant, piezoelectric constant and filtration performance of the fiber membranes of the examples and comparative examples. The fiber membranes of Examples 1 to 5 and Comparative Examples 2 to 3 have a finer fiber diameter (155.7 to 234.2 nm), which is due to the addition of electrolytes to the spinning solution, which increases its conductivity and helps the fiber to be stretched in a high-voltage electrostatic field and thin the fiber. The fiber membranes of Examples 1 to 5 have a higher surface potential (8.9 to 10.7 kV) and dielectric constant (1.61 to 2.73 F / m), which is because the polylactic acid fiber membrane with a core-shell structure and a stereocomplex has a higher electrical activity. The surface potential of Comparative Example 2 is only 1.8 kV, which is because the charge dissipates faster when only right-handed polylactic acid is present. The fiber membranes of Examples 1 to 5 have excellent piezoelectric properties, and the piezoelectric constants are all above 6.6pC / N, especially Example 4, which reaches 8.3pC / N, indicating that the preparation method of the present invention can significantly improve the piezoelectric effect of the fiber membrane by controlling the configuration and crystal structure of the polylactic acid chain.
[0123] The fiber membranes of Examples 1 to 5 have a significant effect on PM 0.3 and PM 2.5 All of them showed excellent filtration performance, especially the fiber membrane of Example 1 for PM 0.3 The filtration efficiency reaches 99.2% for PM 2.5 The filtration efficiency reached 99.8%, and the pressure drop (all <180Pa) was much lower than that of the traditional filtration membrane, indicating that the fiber membrane of the present invention has an extremely high porosity and can significantly reduce the pressure drop of the fiber membrane. 0.3 The filtration efficiency is the lowest, only 69.5%.
[0124] Table 2 compares the test results of output voltage, output current, charge density and filtration performance of the fiber membranes of the embodiments and comparative examples under human breathing simulation. The fiber membranes of embodiments 1 to 5 have higher output voltage, output current (0.87 to 1.12 μA) and charge density (16.5 to 25.3 μC / m 2 ), especially in Example 1, the output voltage reaches 12.4V, the output current reaches 1.12μA, and the charge density reaches 25.3μC / m 2 Compared with the comparative example 1, the output voltage, output current and charge density are increased by 13.8 times, 28.0 times and 24.1 times respectively. At the same time, under the human-like breathing state of 32L / min, the fiber membranes of Examples 1 to 5 have high filtration performance for PM 0.3 The filtration efficiency is greater than 98%, and the PM 2.5The filtration efficiency is greater than 99.7%, and the pressure drop (all <36Pa) is much smaller than that of ordinary commercially available medical masks.
[0125] In summary, the surface potential, dielectric properties, piezoelectric properties and filtration performance of the polylactic acid core-shell structure fiber membrane prepared by the present invention are significantly improved. This is because, through coaxial electrospinning, the introduction of the stereocomplex improves the electrostatic adsorption effect of the fiber membrane, so that the fiber membrane has higher electrical activity and charge storage capacity, thereby ensuring low pressure drop while having higher filtration efficiency; the introduction of electrolyte increases the conductivity of the spinning solution, which helps the fiber to stretch in a high-voltage electrostatic field and make the fiber thinner, thereby improving the filtration performance.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a polylactic acid core-shell structure fiber membrane, characterized in that: The following steps are involved: S1, mixing a first polylactic acid, an electrolyte and a first solvent to obtain a first polylactic acid solution; S2, mixing the second polylactic acid with the second solvent to obtain a second polylactic acid solution; S3, using the first polylactic acid solution and the second polylactic acid solution as a shell layer spinning solution and a core layer spinning solution, respectively, to perform coaxial electrospinning to obtain the polylactic acid core-shell structure fiber membrane; Wherein, the first polylactic acid and the second polylactic acid are each independently selected from at least one of left-handed polylactic acid and right-handed polylactic acid, and the first polylactic acid solution and the second polylactic acid solution are used as a composite solution, and the composite solution contains both the left-handed polylactic acid and the right-handed polylactic acid.
2. The preparation method according to claim 1, characterized in that: The electrolyte includes at least one of potassium chloride, sodium chloride, lithium chloride and calcium chloride.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the first polylactic acid to the electrolyte is (0.1-1):
1.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the first polylactic acid to the second polylactic acid is (0.5-2):1; and / or, In the composite solution, the mass ratio of the L-polylactic acid to the D-polylactic acid is 1:(0-1); Preferably, the first polylactic acid is the L-polylactic acid, and the second polylactic acid is the D-polylactic acid; or, the first polylactic acid is the D-polylactic acid, and the second polylactic acid is the L-polylactic acid; Alternatively, the L-polylactic acid is divided into a first portion of L-polylactic acid and a second portion of L-polylactic acid, the first polylactic acid is the first portion of L-polylactic acid, and the second polylactic acid is a mixture of the second portion of L-polylactic acid and the D-polylactic acid; Alternatively, the L-polylactic acid is divided into a first portion of L-polylactic acid and a second portion of L-polylactic acid, the second portion of L-polylactic acid is the first portion of L-polylactic acid, and the first portion of L-polylactic acid is a mixture of the second portion of L-polylactic acid and the D-polylactic acid; Alternatively, the dextrorotatory polylactic acid is divided into a first portion of dextrorotatory polylactic acid and a second portion of dextrorotatory polylactic acid, the first polylactic acid is the first portion of dextrorotatory polylactic acid, and the second polylactic acid is a mixture of the second portion of dextrorotatory polylactic acid and the laetrorotatory polylactic acid; Alternatively, the dextrorotatory polylactic acid is divided into a first portion of dextrorotatory polylactic acid and a second portion of dextrorotatory polylactic acid, the second portion of polylactic acid is the first portion of dextrorotatory polylactic acid, and the first portion of polylactic acid is a mixture of the second portion of dextrorotatory polylactic acid and the laetrorotatory polylactic acid.
5. The preparation method according to claim 1, characterized in that: The mass fraction of the first polylactic acid in the first polylactic acid solution is 0.1% to 15%; and / or, The mass fraction of the second polylactic acid in the second polylactic acid solution is 0.1% to 15%; and / or, The concentration of the electrolyte in the first polylactic acid solution is 0.01-1 g / mL.
6. The preparation method according to claim 1, characterized in that: The first solvent and the second solvent each independently include at least one of dichloromethane, chloroform, N,N-dimethylformamide, acetone, ethyl acetate, and ethanol.
7. The preparation method according to claim 1, characterized in that: In the coaxial electrospinning process, the metal nozzles for loading the shell layer spinning solution and the core layer spinning solution are respectively the first nozzle and the second nozzle; Preferably, the inner diameter of the first nozzle is 0.5-1 mm, and the inner diameter of the second nozzle is 1.2-1.5 mm; Preferably, the voltage of the first nozzle and the second nozzle is independently 5 to 50 kV; Preferably, the consumption rate of the shell layer spinning solution is 1 to 5 mL / h, and the consumption rate of the core layer spinning solution is 1 to 5 mL / h; Preferably, the receiving distances of the first nozzle and the second nozzle are independently 10 to 50 cm, and the wire collection speed is 100 to 5000 rpm.
8. A polylactic acid core-shell structure fiber membrane, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. The polylactic acid core-shell structure fiber membrane according to claim 8, characterized in that: The average diameter of the fibers in the polylactic acid core-shell structure fiber membrane is 100 to 300 nm; Preferably, the average diameter of the fibers in the polylactic acid core-shell structure fiber membrane is 155-235 nm.
10. A personal protective device, characterized in that: It includes the polylactic acid core-shell structure fiber membrane as described in claim 9.
Citation Information
Patent Citations
Functionalized nano-fiber filter material and preparation method and application thereof
CN108579212A
Preparation method for bio-based degradable polymer superfine fibers
CN111206301A
Nanofiber slow-release carrier material based on core-shell structure and preparation method of nanofiber slow-release carrier material
CN116236462A
Stereocomplex polylactic acid directional moisture-conducting hollow fiber filter membrane and preparation method thereof
CN118949575A
Polylactic acid fiber having stereo complex structure and method for producing the same
JP2007231480A
Cited By
Piezoelectric bionic structure rotator cuff patch and preparation method thereof
CN121490137A